Sensitivity and Specificity of Malaria Rapid Diagnostic Test (RDT) - Siti Retno Yuniatun; Dwi Haryatmi (Indonesian Journal of Global Health Research, 2025)
Malaria remains a significant public health issue in many regions, and early diagnosis is crucial for effective treatment. Rapid Diagnostic Tests (RDT) are commonly used for malaria detection due to their speed and ease of use, but their diagnostic accuracy, particularly in regions with varying levels of parasitemia, remains a subject of ongoing research. This study aimed to evaluate the performance of Rapid Diagnostic Tests (RDT) for malaria diagnosis at Puskesmas Hanura, Teluk Pandan District, Pesawaran Regency, by assessing the sensitivity and specificity of the test. Methods: This analytical observational study employed a cross-sectional approach, analyzing blood samples from malaria suspect patients collected between December 2024 and February 2025, with a total sample size of 50 samples. The diagnostic performance of RDT was compared to the gold standard of microscopy using thick and thin blood smears. Sensitivity and specificity were calculated based on the results of both methods. The sensitivity of the RDT was found to be 93.5%, indicating that the test was highly effective in detecting true positive malaria cases, particularly in individuals with high parasitemia. The specificity was 100%, demonstrating that the RDT accurately identified malaria-free individuals with no false positive results. However, the study also identified two false negative cases, suggesting that the RDT's sensitivity could be reduced in cases of low parasitemia. The Rapid Diagnostic Test demonstrated excellent sensitivity and specificity in detecting malaria at Puskesmas Hanura, with no false positive results and a high rate of true positive detection. However, the test showed some limitations in detecting low parasitemia, emphasizing the need for confirmatory diagnostic techniques, such as microscopy or molecular methods, especially in areas with low transmission or mild infections.